An Error Analysis of Students’ Writing as EFL: A Descriptive Qualitative Research - Irawansyah, Irawansyah (Lingual Journal of Language and Culture, 2024)
Error analysis (hereafter EA) is an essential concept to understand because it frequently comes up in foreign language teaching and learning. This study identified and investigated errors did by Indonesian students according to surface strategy taxonomy (hereafter SST) which classified errors into four kinds, such as omission (OM), addition (AD), misformation (MF), and misordering (MO). To conduct this study, approximately 26 students of English education program, both male and female were participated. The study employed qualitative research. A free writing with the topic of their experience was collected as data collecting. The writer then collected the data, identified, and analysed them by using percentage formula and categorized them to the kinds of errors based on SST. The results showed that the whole errors from students’ writing are 348 errors: omission 8% (27 items), addition 15% (51 tems), misformation 75% (262 items), and misordering 2% (8 items). Therefore, misformations errors is the major errors that common appears in students writing. It is recommended that it is important for the teachers not to ignore students’ errors in English teaching learning process. Keywords : error analysis, surface strategy taxonomy, writing